A Systematic Literature Review of Climate Change Impacts and Adaptation among Older Adults in Malaysia (Journal of Asian Geography, 2025)
The health of the population is increasingly threatened by climate change, with older adults being particularly vulnerable due to changes in their physiological, social, and economic circumstances. In Malaysia, older adults are disproportionately affected by aging, environmental degradation, and extreme temperatures, yet little is known about how these factors interact to impact the country’s aging population. This study aims to conduct a comprehensive assessment of the literature on climate change and the circumstances of older adults in Malaysia, focusing on vulnerabilities, adaptation strategies, and governmental responses. In compliance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a comprehensive literature search was conducted across relevant databases and grey literature. Research suggests that, in the context of climate change, older adults are particularly susceptible to social, economic, and health-related challenges. Despite the presence of informal coping strategies and community-based efforts, there is currently no adequate adaptation strategy in place. Furthermore, existing policies, such as the National Policy on Climate Change and the National Policy on Older Persons, are not consistently aligned to address the combined challenges of aging and environmental degradation. Gaps remain in research and policy development, particularly in the areas of health system resilience, disaster preparedness, and older adults’ involvement in climate policy. To ensure that Malaysia’s aging population is not left behind in the government’s sustainable development objectives, this review underscores the need for age-specific and climate-resilient measures.